A case study on the maintenance and care for textile objects on long-term exhibition in Museo De La Salle - Sestoso, Camille Anne C.
This single-case study analyzed the maintenance and care for textile objects on long-term exhibition in Museo De La Salle. Located within De La Salle University - Dasmariñas, the museum showcases the lifestyle of the Filipino Ilustrado class through a recreation of 19th and early 20th century interiors furnished with antique heirlooms. Exploratory in its approach, this study conducted observation and semi-structured interviews with museum staff over multiple visits. Textile objects were selected to represent a range of types, conditions and display methods. Historical garments, albeit their discolorations, have retained their form, and are mounted on mannequins. Some more sensitive pieces are laid flat on a bed or table as part of the curation of depicting a lived house. Upholsteries are in relatively good condition, while draperies have signs of tearing and fraying. Most textile objects are exhibited in the second-floor rooms, which are naturally ventilated, and their windows are closed to prevent sunlight from coming in. Maintenance and care are focused on regular housekeeping, general inspection, preventive measures, and managing the pathway of visitors. However, rooms are not equipped with environmental monitoring devices, and the museum staff allow the objects to adapt to their current environment. They practice minimal handling and intervention, but rarely accomplish documentation and condition reports. These issues in the current maintenance practices stem from time constraints and multiple priorities of the museum’s limited staff. There is a lack of expertise, as well as adequate space, to conduct condition assessment and remedial conservation of textile objects. This case study underscores the importance of balancing exhibition and conservation. Future research can explore strategies that effectively integrate both in the management of historical house museums in the Philippines.